Social Trajectories and Labor Market Insertion of Colombian Professionals of African Descent. Social Inequality and Racial Discrimination - Bermúdez-Rico, Rosa Emilia; Caicedo-Riascos, Maritza (Sociedad y Economía, 2022)
This article analyzes various social trajectories and experiences in the labor market insertion of professionals who accessed higher education through preferential quotas for Afro-descendant ethnic adscription granted by the Universidad del Valle in Cali-Colombia. The analysis is based on information about graduates of this University and information collected through 22 interviews with Afro-descendant graduates between 2008 and 2018. It identifies mechanisms of resistance and adaptation to overcome inequalities, and face discrimination in the professional labor market and establishes two types of social trajectories and labor insertion that articulate the ethno-racial identity experience and the subjective condition concerning racial discrimination in professional performance. It contributes to the debate on the scope and alternatives of equality of positions and opportunities in the social ascent of the Afro-Colombian population and the configuration of racial identity.